Development of detection methods for 31 pesticide and veterinary drug residues in bee products from Chongqing and their risk assessment of dietary exposure - WU Rong, HE Lingzhi, TAN Meiling, ZHANG Hua, YAN Rui (Zhongguo niangzao)
An ultra high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method was established for the determination of 31 pesticide and veterinary drug residues in bee products, and then the residues were analyzed in 206 bee products from various districts and counties in Chongqing, as well as their dietary exposure risk was assessed. The results showed that samples were extracted with 80% acetonitrile-water (containing 0.2% formic acid), purified by Oasis PRiME HLB solid phase extraction column at the filtration rate of 1 drip/s, separated with Waters ACQUITY UPLC BEH C18 column (100 mm×2.1 mm, 1.7 μm) using methanol and 5 mmol/L ammonium acetate-0.1% formic acid-water solution as the mobile phase for gradient elution, qualified using multiple reaction monitoring (MRM) mode with electrospray ionization in positive and negative ion mode, and quantified with external standard method. Under these conditions, the 25 veterinary drug and 6 pesticides residues showed good linear relationships in the range of 0.2-250 ng/ml and 1.0-250 ng/ml, respectively (R2>0.99), their detection limits, quantitation limits, standard recovery rates and relative standard deviations of precision tests results were 0.006-0.057 μg/kg, 0.021-0.191 μg/kg, 60.3%-116.7%, and 0.3%-13.2%, respectively, indicating that the method had high accuracy and good repeatability, and was suitable for the determination of the pesticide and veterinary drug residues in bee products. A total of 19 pesticide and veterinary drug residues were detected in commercially available bee products, among which the food safety index (IFS) of enrofloxacin, trimethoprim, lornidazole, ciprofloxacin, chloramphenicol and metronidazole were greater than 1, indicating a high risk of dietary exposure and should be strengthened supervision. The results provided references for bee products quality supervision in Chongqing.